Learning through Communication in the EFL Class: Going beyond the PPP Approach. - Herazo Rivera, José David; Jerez Rodríguez, Sonia María; Lorduy Arellano, Danilza (Íkala, Revista de Lenguaje y Cultura, 2009)
Today, it seems clear that the goal of English as a foreign language (EFL) teaching and learning in Colombia is to foster communicative ability. However, the role communication is usually given in classrooms, that of displaying previously taught language items, poses limitations on the value it might have for developing EFL proficiency. In this paper, we disagree with the assumption that communication can only take place when learnershave learned and defend the position that it might happen when learnersare learning. Our position is supported with grounded theoretical reflection as well as with data coming from the EFL class of a group of sixth graders during an ongoing action research project on the use of task-based learning (TBL) to develop citizenship and EFL proficiency. Received: 20-02-09 / Accepted: 14-09-09 How to reference this article: Herazo, J. D., Jerez, S. & Lorduy Arellano, D. (2009). Learning through Communication in the EFL Class: Going beyond the PPP Approach. Íkala. 14(3), pp.117-136.